EFFECT OF COMMUNICATION AND WORK ENVIRONMENT ON EMPLOYEE MOTIVATION IN THE MINING COMPANY PT. SAMANTAKA BATUBARA RIAU - Dominicus Josephus Swanto T; Hidayat Syahputra; Ria Darmasari; Nicholas Renaldo; Ermina Rusilawati (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2024)
The influence of communication and work environment on employee performance is an important factor to increase an effective and growing company. In this study there are problems that the researchers found. The object of this research is PT, Samantaka Batubara Riau. Based on the initial observation that the number of employees of PT. Samantaka Batubara Riau numbered 44 people consisting of various divisions. But what is very unfortunate is that from 2016-2020 the number of employees at PT. Samantaka Batubara Riau has the same amount but the company's results are inconsistent and priceless. The news that circulated at the beginning was due to communication factors and an uncomfortable environment that was present every year so that it affected employee performance so that the researchers were interested in researching more deeply to find out the effect of communication on employee performance at PT. Samantaka Batubara Riau and the influence of the work environment on the performance of employees of PT. Riau Coal Samantaka. This research uses empirical study methods and field studies using questionnaires and the results obtained are that effective communication greatly affects the workings of the company. Communication is a vital communication tool in work besides the work environment also greatly affects employee productivity. There needs to be awareness from the company to see this influence so that the company can also advance and develop